Lysyl oxidase deficiency: a new cause of human arterial dissection. Issue 5 (14th April 2005) - Sibon, I; Sommer, P; Lamaziere, J M Daniel; Bonnet, J
Abstract : Spontaneous coronary artery dissection is a rare cause of myocardial ischaemia. The underlying mechanism is unknown but some dissections are associated with extracellular matrix disorganisation of genetic origin. A deficiency in extracellular matrix protein cross links has rarely been studied. A single clinical case of spontaneous coronary artery dissection is reported. Lysyl oxidase (LOX) and extracellular matrix organisation were investigated by skin immunohistology and polymerase chain reaction of LOX expression. Both approaches found a dramatic LOX decrease. LOX deficiency has a major role in human arterial wall organisation during development. The suspected mechanism is an elastin or collagen polymer cross linking deficiency.